Pengobatan Resistensi Antipsikotik Pada Pasien Skizofrenia - Afrina Zulaikha; Muhammad Hafazdh Furqani (Institut Nalanda, 2024)
Schizophrenia is a disorder with a heterogeneous etiology that includes patients with varying clinical presentations, responses to therapy and disease courses. One therapy for treating schizophrenic patients is to use typical and atypical antipsychotics. However, patients who initially respond to antipsychotic drugs can become resistant (Treatment Resistance Schizophrenia).